2022
DOI: 10.3389/fpsyg.2022.1009800
|View full text |Cite
|
Sign up to set email alerts
|

Online in-class vs. out-of-class flipped learning models in English as foreign language writing classes

Abstract: Flipped learning models are considered as important elements of English as a foreign language (EFL) writing courses in order to advance the EFL learners' writing skills. Significantly, studies examining the efficacy of in-class and out-of-class writing models in flipped classroom settings when teaching online EFL writing courses are still of focus in the Turkish Cypriot context. This investigation aimed to examine the most efficient flipped learning model among the in-class vs. out-of-class writing models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Metacognition is both the basis and the result of the development of the intellectual and creative potential of the individual, including the younger student (Fleur, et al, 2021). Psychological, neurophysiological, and social characteristics of younger schoolchildren provide significant advantages for starting to learn a foreign language, since at this age children absorb linguistic features indirectly, through the development of a system of thinking skills (Gutierrez de Blume et al, 2023;Fu et al, 2023;Sengul et al, 2022). Moreover, the effectiveness in this case is very conditional, since the effectiveness of the development of metacognitive skills in a particular case can be revealed by a formalized assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metacognition is both the basis and the result of the development of the intellectual and creative potential of the individual, including the younger student (Fleur, et al, 2021). Psychological, neurophysiological, and social characteristics of younger schoolchildren provide significant advantages for starting to learn a foreign language, since at this age children absorb linguistic features indirectly, through the development of a system of thinking skills (Gutierrez de Blume et al, 2023;Fu et al, 2023;Sengul et al, 2022). Moreover, the effectiveness in this case is very conditional, since the effectiveness of the development of metacognitive skills in a particular case can be revealed by a formalized assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies prove that multilingual education contributes to the intensification of mental development, especially when solving tasks that require originality of thinking and intellectual flexibility, based on interdisciplinary knowledge (Nijiati et al, 2020;Zhang and Zhang 2019;Lin et al, 2021;Sengul et al, 2022;Yamada 2018). Psychological, neurophysiological, and social characteristics of younger schoolchildren provide significant advantages for starting to learn a foreign language, since at this age children absorb linguistic features indirectly, through the development of a system of thinking skills (Karabulatova et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have explored the impact of FC on students' writing skills. Research has demonstrated that it effectively supports students in adopting the process writing approach, accommodating diverse learning styles (Sengul et al, 2022). Baranovic (2013) Studies by Abedi et al (2019), Florence (2020), Gürlüyer andElkılıç (2020), andIndayani et al, (2022) examined the impact of FC on EFL learners' writing sub-skills.…”
Section: Flipped Classroom and Teaching Writingmentioning
confidence: 99%